Analysis of Nanoarchaeum equitans genome and proteome composition: indications for hyperthermophilic and parasitic adaptation - Bag Sumit K; Paul Sandip; Das Sabyasachi; Dutta Chitra (BMC Genomics, 2006)
Abstract Background Nanoarchaeum equitans, the only known hyperthermophilic archaeon exhibiting parasitic life style, has raised some new questions about the evolution of the Archaea and provided a model of choice to study the genome landmarks correlated with thermo-parasitic adaptation. In this context, we have analyzed the genome and proteome composition of N. equitans and compared the same with those of other mesophiles, hyperthermophiles and obligatory host-associated organisms. Results Analysis of nucleotide, codon and amino acid usage patterns in N. equitans indicates the presence of distinct selective constraints, probably due to its adaptation to a thermo-parasitic life-style. Among the conspicuous characteristics featuring its hyperthermophilic adaptation are overrepresentation of purine bases in protein coding sequences, higher GC-content in tRNA/rRNA sequences, distinct synonymous codon usage, enhanced usage of aromatic and positively charged residues, and decreased frequencies of polar uncharged residues, as compared to those in mesophilic organisms. Positively charged amino acid residues are relatively abundant in the encoded gene-products of N. equitans and other hyperthermophiles, which is reflected in their isoelectric point distribution. Pairwise comparison of 105 orthologous protein sequences shows a strong bias towards replacement of uncharged polar residues of mesophilic proteins by Lys/Arg, Tyr and some hydrophobic residues in their Nanoarchaeal orthologs. The traits potentially attributable to the symbiotic/parasitic life-style of the organism include the presence of apparently weak translational selection in synonymous codon usage and a marked heterogeneity in membrane-associated proteins, which may be important for N. equitans to interact with the host and hence, may help the organism to adapt to the strictly host-associated life style. Despite being strictly host-dependent, N. equitans follows cost minimization hypothesis. Conclusion The present study reveals that the genome and proteome composition of N. equitans are marked with the signatures of dual adaptation – one to high temperature and the other to obligatory parasitism. While the analysis of nucleotide/amino acid preferences in N. equitans offers an insight into the molecular strategies taken by the archaeon for thermo-parasitic adaptation, the comparative study of the compositional characteristics of mesophiles, hyperthermophiles and obligatory host-associated organisms demonstrates the generality of such strategies in the microbial world.